Inventory visibility scenario to reduce safety stock in supply chain network using blockchain hyperledger composer - Arwa, Mukhtar; Awanis, Romli; Noorhuzaimi@Karimah, Mohd Noor; Mansoor, Abdullateef; Al-Bashiri, Hael (2012)
Limited inventory visibility in supply chain networks increases stock levels and leads to negative consequences of stock repetition, bullwhip‐effect, inventory backlog, and out of stock situations. It is essential to increase the inventory visibility and reduce the safety stock level to exchanged inventory data between supply chain stakeholders to achieve inventory accuracy and efficiency accordingly. This paper presents a technical implementation of inventory visibility scenario to reduce safety stock level in Blockchain-based supply chain network. The proposed inventory visibility scenario provides access to accurate and up to date inventory levels and reduces the safety stock level accordingly. The scenario implemented using Blockchain Hyperledger Composer and tested in Blockchain Hyperledger Composer Bluemix. In the performance evaluation, the inventory visibility scenario compared to Cloud-based and traditional supply chain models in terms of reducing the safety stock level. Scenario results show improved inventory visibility and significant reduction in inventory safety stock compared to other models. This reduction prevents negative consequences of stock repetition, bullwhip‐effect, inventory backlog, and out of stock situations which helps in efficient inventory management and hence improves supply chain performance.